An innovative compound bed of EDI device with enhancing ion-exchange resins regeneration efficiency - Xu Chen (IWA Publishing, 2021)
Electrodeionization (EDI) technology is limited by low regeneration efficiency of ion exchange resins, requirements of high-quality influent water, fouling of the ion exchange membrane and electrode, etc. In this work, a novel bed type called a compound bed in which cation and anion exchange resins were near the cation and anion exchange membrane and placed in layers, was proposed to implement high-efficiency regeneration of ion exchange resins. The influence of different operating conditions on the regeneration efficiency of ion exchange resins was elucidated as well. The regeneration efficiency of ion exchange resins could reach 73.1%, when the device was operated for 5 h under current density of 9 mA/cm2, with a cation and anion exchange resins ratio of 2: 3, influent water conductivity of 1,360 μS/cm and hardness of 400 mg/L. Therefore, the proposed compound bed structure not only widened the inlet water conditions, but also achieved the high-efficiency regeneration of ion exchange resins and anti-fouling of membranes and electrodes. HIGHLIGHTS A novel bed type called a compound bed (CB) was proposed.; CB structure facilitated water dissociation reaction and shortened the path of ion migration.; Optimized CB structure possessed high regeneration efficiency of ion exchange resins.; Optimized CB structure conferred anti-fouling performance on this device.;